A Case Study of a Healthcare System in The North East Nigeria: Supply Chain Innovation as A Sustainable Strategy for Health Care Operation in Nigeria - Ahmed Balami, Samuel (Journal of Cross-Disciplinary Sustainability Innovations, 2025)
Prolonged fighting and insecurity in Nigeria's North-East have greatly damaged healthcare systems, so aggravating already-existing problems in supply chain management and limiting access to vital medical commodities. This case study looks at how supply chain technologies are applied as a sustainable solution for healthcare activities inside this difficult setting. Concentrating on a particular regional healthcare system, we examine the key tactics that the Nigerian health industry should emphasis in order to attain supply chain innovation success, how technology innovation help in Nigerian Healthcare operations. Use and effect of innovative techniques distribution strategies. The research investigates how these advances improve the equity, resiliency, and efficiency of healthcare supply chains, hence increasing medicine and medical equipment availability. Initial results indicate that negotiating the particular logistical challenges in conflict-affected areas depends on strategic investments in data analytics, last-mile delivery systems, and local capacity development. Highlighting the potential of these creative approaches to not only repair but also improve healthcare delivery, the abstract concludes with a roadmap for sustainable healthcare activities in Nigeria and other sensitive. The research contributes to the discourse on global health equity by presenting a contextual understanding of how supply chain innovation can mitigate health disparities in resource-constrained and conflict-affected regions. It also emphasize the limitations for this research that actually can be done more, sociopolitical instabilities, and endemic public health challenges. Furthermore, by evaluating real-world implementation, this study underlines the practical feasibility of transformative supply chain frameworks across similar developing nations.